Isolation and Characterization of Compounds from the Leaves of Pterocarpus indicus Willd and Their Antioxidant Activity - Hartati, Sri; Angelina, Marissa; Meilawati, Lia; Dewijanti, Indah Dwiatmi (ANNALES BOGORIENSES, 2016)
The flavone glycoside was isolated from ethyl acetate fraction of ethanol extract of leaves Pterocarpus indicus Willd. The isolation was conducted by gravitation column chromatography and eluted successively with hexane, ethyl acetate and methanol by gradient, and purified by sephadex-LH20. The structure was elucidated base on spectroscopy data of NMR (1D and 2D), UV, LC-MS and FT-IR. Antioxidant was evaluated using 2,2-diphenyl-1-picrylhidrazyl (DPPH) radical scavenging. The isolation and identification led a stigmasterol as Compound 1 and a new flavonol-glycoside [(2R)-7-hydroxy-3-(3,4,5-trihydroxy-6-(hydroxymethyl)tetrahydro-2H-pyran-2-yloxy)-2-(3,4,5-trihydroxy phe nyl)chroman-4-one] or ptevon-3-D- glycoside as Compound 2. Antioxidant activity of Compound 2 showed IC50 for 18.53 mmol and blank of quercetin was 7.94 mmol and Vitamin C was 40.25 mmol. These compounds and antioxidant activities are the first time reported from this plant.Â